Nursing interventions based on the knowledge-attitude-practice model on anxiety and treatment compliance in an elderly patient with Ramsay-Hunt Syndrome and vestibular neuritis (知信行理论模式干预1例耳带状疱疹合并前庭神经炎老年患者焦虑情绪和治疗依从性的护理体会) - CAO Haiyan (曹海燕); XU Ling (徐玲); YANG Hui (杨惠); LI Qingqing (李青青) (中西医结合护理)
This paper summarized the nursing interventions based on the knowledge-attitude-practice model on anxiety and treatment compliance in an elderly patient with Ramsay-Hunt Syndrome and vestibular neuritis. This elderly female patient was diagnosed as vertigo of wind-Yang disturbance syndrome by Traditional Chinese Medicine syndrome differentiation, and she was suffered from anxiety and low treatment compliance. Based on the Traditional Chinese Medicine syndrome differentiation, nursing interventions based on the knowledge-attitude-practice model were carried out to relieve the anxiety and improve the treatment compliance. The Self-rating Anxiety Scale score dropped form 60 to 25 before discharge form hospital. The Morisky medication adherence scale score increased from 2. 5 to 8, indicating a improved level of medication adherence of the patient after intervention. (本文总结基于知信行理论(KAP)模式干预1例耳带状疱疹合并前庭神经炎老年患者焦虑情绪和治疗依从性的护理体会。本例高龄女性患者中医诊断为眩晕(风阳上扰证), 且存在焦虑情绪和治疗依从性差的问题。基于中医辨证分型, 运用KAP模式进行护理干预。患者焦虑自评量表(SAS)评分从60分(轻度焦虑)降低至25分(无焦虑), 焦虑情绪得到改善; Morisky服药依从性量表评分从2. 5分上升至8分, 治疗依从性得到提高。)